Requalification as a labor market demand and life strategy in the post-industrial society - A. S. Barkova (RUDN journal of Sociology, 2025)
Requalifi has become especially relevant in the contemporary postindustrial society characterized by dynamic social-technological changes, labor market transformation and, consequently, the need for professional adaptation. The article presents a comprehensive analysis of this social-economic phenomenon in today’s realities, under technological innovations, automation of production processes and globalization of economic relations radically changing the requirements for professional competencies. Methodological diffi in the study of requalifi are determined by the lack of its common understanding. The analysis of Russian and foreign research data shows that “requalifi and “professional retraining” are often perceived as synonyms, which distorts statistical data. An important research problem is the lack of systematic mechanisms for recording cases of a complete change of profession. As a rule, labor market monitoring systems record only facts of professional mobility without diff them by specifi areas/specialization or degree of change, which signifi limits opportunities for the analysis of effi of various models of professional adaptation. Requalifi is a complex multidimensional process that can be forced or proactive, full (cardinal change of professional sphere) or partial (expanded or deepened competencies). This phenomenon is closely related to various forms of professional mobility: upshifting (a higher professional position), downshifting (conscious decline in professional status) and horizontal. Each of these forms refl diff strategies of adaptation to changing labor market conditions and personal professional aspirations, thus, demonstrating the diversity of professional trajectories in the contemporary economy. Despite many vivid examples of successful career change, a systematic analysis of secondary data and surveys reveals a paradoxical trend: many people want to change their profession, but the majority of those who decided on radical retraining remain dissatisfi with its results, and this contradiction between media success stories and real situation requires further analysis. At the same time, the highest level of professional satisfaction is observed among workers who managed non-radical requalifi doctors who changed their fi of activity or drivers who changed their type of vehicle.